Web Based UCloud Application Using CodeIgniter Framework - Valian Yoga Pudya Ardhana; Muh Sapi'i; M. Dermawan Mulyodiputro (SainsTech Innovation Journal, 2021)
Internet-based data storage services or called the cloud are becoming a global technology trend, the cloud that offers unlimited scalability is becoming very reliable. Educational institutions such as Qamarul Huda Badaruddin University are always constrained by poor data management because there is no centralized data storage area that can be accessed together. With the presence of UCloud, data management problems can be resolved. Designed using the web-based CodeIgniter framework, Ucloud has been successfully implemented and optimally utilized by the academic community, so that data can be managed properly.